Improving student learning outcomes through the inquiry learning model with powtoon animation on plane geometry subject - Safitri, Asri Dwi; Rusnilawati, Rusnilawati (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
The objective of the study is to illustrate how the enactment of the inquiry learning model with Powtoon animation impacts the enhancement of student learning outcomes in the plane geometry subject. This study utilizes a quantitative method employing a quasi-experimental design.  The sampling method applied is cluster random sampling, involving two groups for the study: the experimental group and the control group, serving as the comparative sample.  The sample for the study comprises 52 fifth-grade students, with each class containing 26 students. Data collection instruments include test sheets, observation sheets, and documentation. Data analysis techniques in statistical tests include instrument validity testing, instrument reliability testing, prerequisite testing, dependent t-test, independent t-test, and N-Gain test. Learning outcomes after implementing the inquiry learning model with Powtoon animation media were significantly different compared to before implementation.  Moreover, there was a notable distinction in learning outcomes observed between the control and experimental groups. The average posttest score for the experimental group stood at 74,04, whereas for the control group, it was 61,69. The influence of the inquiry learning model with Powtoon animation media reached a moderate category. Involving technology such as Powtoon animation in inquiry-based learning can generate interest in learning, thus affecting the improvement of student learning outcomes.